Predictive intelligence for a rail traffic management system - Roberts, Simon; Bonenberg, Lukasz; Meng, Xiaolin; Moore, Terry; Hill, Chris (2017)
As the demands on terrestrial transport systems increase, there is a growing need for greater efficiencies. More intelligent mobility and ultimately autonomous transport assets will deliver these efficiencies through the evolution of cooperative intelligent transport system (C-ITS) technology. Central to this evolution will be the capability to accurately and precisely position assets within their environment and relative to each other to predefined and regulated standards.